Excavations at the Mycenaean Cemetery at Aigion - 1967 : rescue excavations by the late Ephor of Antiquities, E. Mastrokostas - Papadopoulos, Thanasis J., (Archaeopress Publishing Ltd, 2017)
In this monograph the authors present the finds of four Mycenaean chamber tombs, from the rescue excavation of Ephor Mastrokostas at Aigion in 1967.